The main directions of reconstruction of repair shops - Дашивець, Галина Іванівна; Dashyvets, Halyna; Shyrochkin, V. (Запоріжжя : ТДАТУ, 2023)
EN: The Ukrainian economy suffered significant losses. But the war already raises the issue of post-war reconstruction, taking into account construction and dismantling works, waste processing. One of the main principles of restoration is optimized project solutions, which include the implication of waste, the ability to reconstruct, add to, and change the functionality of buildings; modularity and unification of structures; compatibility and interchangeability when used as necessary for another purpose [1]. All these measures also apply to the repair and maintenance base of the agricultural industry. Reconstruction projects are developed after an examination of the existing repair shop, which determines its physical wear and tear. The drawings of the inspected buildings must contain the characteristics of the main structures. The survey of the production activity of the main parts of the workshop consists in the collection of materials characterizing the existing technological process, operating equipment and technical and economic efficiency of production.
Keywords: application of the block-module; construction and reconstruction of repair shops of agricultural enterprises is; design; typical workshop projects for farms